ANALISIS STRATEGI BAURAN PEMASARAN KRIPIK USUS RAMADHAN PADA MASA PANDEMI COVID-19 - Jamil, S. Hikmah; Rofiqoh, Ainur; Wildani, Melly (Al-Musthofa: Journal of Sharia Economics, 2022)
The purpose of the study was to find out the marketing mix strategy carried out by theRamdhan intestine chips business during the covid-19 pandemic. The COVID-19 pandemic has had aprofound impact on various fields. Both health, politics, education, and economy. During the COVID-19pandemic, it has had an impact on small and large scale businesses. Many workers have been laid off orlaid off as a result of declining purchases by consumers. This research approach uses a qualitative descriptivemethod. From this research, it can be concluded that although the covid-19 pandemic also has an impact onthe Ramadhan intestine chips business, this business can still survive and even increase sales byimplementing a marketing mix strategy which consists of 4 marketing mix variables, namely product, price,promotion.Keywords: Marketing Mix Strategy, Product, Covid-19 Pandemic